Analysis and application of friction calculation model for long-distance rock pipe jacking engineering. (September 2021) - Deng, Zhiyun; Liang, Ninghui; Liu, Xinrong; de la Fuente, Albert; Lin, Peng; Peng, Haoyang
Highlights: Influence factors of pipe-rock friction resistance in rock stratum are analyzed. The friction calculation model for rock pipe jacking engineering is established. The calculation model for pipe-rock friction resistance is verified by field data. The combined calculation model is applied to guide the timely removal of sediment. Abstract: For long-distance rock pipe jacking, the coupled actions of mud float and sediment generate pipe-rock interactions, which are challenging from the analysis point of view and the general methods available for calculating the friction resistance of pipe-soil can lead to unrepresentative results. These friction forces must be quantified properly, as the magnitude of those determines the technical and economical construction requirements. In this regard, a novel approach that combines experimental and numerical stages is proposed in this research paper for dealing with the assessment of these friction forces. The results derived from the proposed approach were compared and validated with others obtained from a practical case, with satisfactory outcomes. The approach proposed herein is found to be a valuable guide for assessing the magnitude of the frictional forces that occur during the pipe jacketing and for identifying the parameters that govern the magnitude of these forces. Eventually, design and construction optimization and productivity-oriented measures can be derived from the application of the method.